A Desktop Study to Determine Mineralization Using Lineament Density Analysis at Kulon Progo Mountains, Yogyakarta and Central Java Province, Indonesia - Okki Verdiansyah (Indonesian Journal of Geography, 2019)
A geological study was conducted in Kulon Progo and its surrounding areas (Kulon Progo and Purworejo Regency). It focused on regional geology, tectonic configuration, geodynamics and magmatism, lithology and volcanology, and mineralization. Although there has been considerable research of mineralization in the area—particularly in Kokap (Kulon Progo Regency), Bagelen (Purworejo Regency) and Gupit (Magelang Regency), the potential of precious metals has not been determined due to data limitations. The study combined qualitative and semi-quantitative methods using a desktop geologic analysis, which facilitates lithology interpretation, volcanic boundary system, and lineament density assessment. The geology of the region is composed of an ancient volcanic complex of the Old Andesite Formation formed during the Late Oligocene-Miocene, and the mineralization in Kokap, Bagelen, and Gupit is epithermal. Based on the analysis results, the mineralization occurs in the central to proximal facies of the paleo-volcano, and the system ranges from 2.2 to 3.8 km in diameter. The manual analysis of the lineament density showed that the main direction of the lineaments was SE-NW with a maximum density of 2025.9 m/km2 and an anomaly limit of >1800 m/km2. In the combined semi-automatic analysis, the maximum density was 8.3 km/km2. The target area of mineralization included four anomalous areas, namely Bagelen-Kokap, Salaman, Kaligesing, and Loano, associated with the central and proximal facies of each small paleo-volcano.